The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Publisher: Routledge
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Krafft, Bjørn; Kirkman, Stephen; Bester, Marthán; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2005)
Antarctic fur seal Arctocephalus gazella pup production at Nyrøysa, Bouvetøya was estimated to be approximately 15,000 per annum during each of four summers from 1996 to 2002, indicating a total population of about 66,000. While the Bouvetøya population is the second largest for this species, pup production at this site still accounts for only 2.4% of the global total. This population experienced a mean annual rate of increase of 30.6% for the period 1989–1996, perhaps due, in part, to significant immigration, but has been stable since 1996. Historical accounts of significant numbers of animals being present towards the end of the period of sealing (C.1800–1930), indicate that the geographic isolation and inaccessibility of this site may have resulted in the Bouvetøya population being one of three populations that survived a series of periods of extreme exploitation of this species.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis